2011
DOI: 10.2131/jts.36.851
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated silencing of the gene for heat shock transcription factor 1 causes hypersensitivity to methylmercury in HEK293 cells

Abstract: -Methylmercury is a hazardous heavy metal compound that can damage the central nervous system. The mechanisms of methylmercury toxicity and the biological defense mechanisms against it remain unclear. We employed gene knockdown using siRNA to search for transcription factors involved in the manifestation of methylmercury toxicity. We found that the inhibition of expression of the gene for heat shock transcription factor 1 (HSF1) sensitized HEK293 cells to methylmercury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Furthermore, the research group led by Dr. Naganuma has found a large number of proteins that are resistant or hypersensitive to MeHg (Hwang et al, 2007(Hwang et al, , 2010a(Hwang et al, , 2010b(Hwang et al, , 2010c(Hwang et al, , 2011b(Hwang et al, , 2012a(Hwang et al, , 2012b(Hwang et al, , 2013b. For example, they found that L-glutamine:D-fructose-6-phosphate amidotransferase (GFAT), which is an essential enzyme for catalyzing the synthesis of glucosamine-6-phosphate from glutamine and fructose-6-phosphate, is a factor that confers MeHg-resistance and that GFAT is the intracellular target molecule for MeHg toxicity Naganuma et al, 2000).…”
Section: Attempts To Identify Cases Of the S-mercuration Of Proteinsmentioning
confidence: 99%
“…Furthermore, the research group led by Dr. Naganuma has found a large number of proteins that are resistant or hypersensitive to MeHg (Hwang et al, 2007(Hwang et al, , 2010a(Hwang et al, , 2010b(Hwang et al, , 2010c(Hwang et al, , 2011b(Hwang et al, , 2012a(Hwang et al, , 2012b(Hwang et al, , 2013b. For example, they found that L-glutamine:D-fructose-6-phosphate amidotransferase (GFAT), which is an essential enzyme for catalyzing the synthesis of glucosamine-6-phosphate from glutamine and fructose-6-phosphate, is a factor that confers MeHg-resistance and that GFAT is the intracellular target molecule for MeHg toxicity Naganuma et al, 2000).…”
Section: Attempts To Identify Cases Of the S-mercuration Of Proteinsmentioning
confidence: 99%
“…The siRNA-transfected cells were plated into single wells of 12-well plates and cultured for 72 hr. Total RNA was isolated using Isogen reagent (Nippon gene, Tokyo, Japan) according to the manufacturer's protocol (Hwang et al, 2010(Hwang et al, , 2011. First strand cDNA was synthesized using the PrimeScript TM RT reagent kit (Takara, Shiga, Japan).…”
Section: Sirna Transfection and Quantitative Real-time Pcrmentioning
confidence: 99%
“…As well, correlations between high expression of HSF1 mRNA with cancer grade, metastasis, and poor prognosis suggest that it has a role in tumor progression. Several examples of the effect of silencing this gene in different cancer types have been revealing an increase of apoptosis, a reduction or inhibition of the tumor growth, a decrease in cancer cells proliferation, and an inhibition of cellular transformation and tumorigenesis, once more attesting its relevance in cancer disease [68,71,72,73]. …”
Section: Combinatory Approachesmentioning
confidence: 99%